Glucose Homeostasis - Szablewski, Leszek (IntechOpen, 2014)
Most tissues and organs, such as the brain, need glucose constantly, as an important source of energy. The low blood concentrations of glucose (hypoglycemia) can cause seizures, loss of consciousness, and death. On the other hand, long lasting elevation of blood glucose concentrations (hyperglycemia) can result in blindness, renal failure, cardiac and peripheral vascular disease, and neuropathy. Therefore, blood glucose concentrations need to be maintained within narrow limits. The process of maintaining blood glucose at a steady-state level is called glucose homeostasis. This is accomplished by the finely hormone regulation of peripheral glucose uptake (glucose utilization), hepatic glucose production and glucose uptake during carbohydrates ingestion.